1991
DOI: 10.1126/science.1704150
|View full text |Cite
|
Sign up to set email alerts
|

Inability of Malaria Vaccine to Induce Antibodies to a Protective Epitope Within Its Sequence

Abstract: Saimiri monkeys immunized with a recombinant protein containing 20 copies of the nine amino acid repeat of the Plasmodium vivax circumsporozoite (CS) protein developed high concentrations of antibodies to the repeat sequence and to sporozoites, but were not protected against challenge. After intravenous injection of an immunoglobulin G3 monoclonal antibody (NVS3) against irradiated P. vivax sporozoites, four of six monkeys were protected against sporozoite-induced malaria, and the remaining two animals took si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 21 publications
0
46
1
Order By: Relevance
“…Here we have made the important advance of achieving broad antibody responses using clinically relevant adjuvant materials. Previous studies using recombinant proteins or multipeptide constructs to target multiple vivax CSP regions showed evidence of immunodominance with some peptide combinations, with antibody responses focused on only a single epitope (19) or responses that failed to bind the critical protective AGDR sequence (26). Although the precise mechanism underlying NP-mediated broadening of the antibody response is the subject of further studies beyond the scope of this first report, we speculate that multivalent display of VMP001 on ICMVs may stimulate a more diverse set of naïve B cells, by allowing some lower-avidity B cells to compete for the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have made the important advance of achieving broad antibody responses using clinically relevant adjuvant materials. Previous studies using recombinant proteins or multipeptide constructs to target multiple vivax CSP regions showed evidence of immunodominance with some peptide combinations, with antibody responses focused on only a single epitope (19) or responses that failed to bind the critical protective AGDR sequence (26). Although the precise mechanism underlying NP-mediated broadening of the antibody response is the subject of further studies beyond the scope of this first report, we speculate that multivalent display of VMP001 on ICMVs may stimulate a more diverse set of naïve B cells, by allowing some lower-avidity B cells to compete for the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Fragments N and C include functional domains (RI and RII plus) that bind to hepatocyte ligands and are involved in sporozoite invasion of the hepatocyte, [17][18][19] whereas the central repetitive domain represented by peptide R has been shown to contain B cell epitopes 16 able to induce invasion-blocking antibodies. 20 Preclinical studies conducted by our group in mice and Aotus monkeys have indicated that the synthetic peptides described are safe and immunogenic in animal models. 21,22 We report here the results of a randomized, double-blind, phase I clinical trial conducted in healthy, malaria-naive volunteers at the Malaria Vaccine and Drug Development Center in Cali, Colombia.…”
mentioning
confidence: 99%
“…2D to F), in particular to the AGDR motif within the type 1 repeat sequence, are thought to play an important role in protection (7,34). All monkeys generated responses to the type 1 repeat peptide.…”
Section: Resultsmentioning
confidence: 99%